1996
DOI: 10.1016/s0092-8674(00)81308-2
|View full text |Cite
|
Sign up to set email alerts
|

Site-Specific Ribose Methylation of Preribosomal RNA: A Novel Function for Small Nucleolar RNAs

Abstract: Eukaryotic cells contain many fibrillarin-associated small nucleolar RNAs (snoRNAs) that possess long complementarities to mature rRNAs. Characterization of 21 novel antisense snoRNAs from human cells followed by genetic depletion and reconstitution studies on yeast U24 snoRNA provides evidence that this class of snoRNAs is required for site-specific 2'-O-methylation of preribosomal RNA (pre-rRNA). Antisense sno-RNAs function through direct base-pairing interactions with pre-rRNA. The antisense element, togeth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
753
1
7

Year Published

1997
1997
2002
2002

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 775 publications
(773 citation statements)
references
References 65 publications
12
753
1
7
Order By: Relevance
“…The nucleolus is a prominent organelle in the nucleus of eukaryotic cells+ It is the site of ribosome biogenesis, which involves ribosomal RNA (rRNA) synthesis, modification and processing, and association with ribosomal proteins+ Several of these events are mediated by small nucleolar RNAs (snoRNAs)+ There are about 200 snoRNA species in the nucleolus, most of which are used to guide the modifications that occur on pre-rRNA: 29-O-ribose methylation by snoRNA members of the Box C/D family (Cavaillé et al+, 1996;Kiss-László et al+, 1996Maden, 1996;Nicoloso et al+, 1996;Tollervey, 1996;Tycowski et al+, 1996;Maden & Hughes, 1997;Smith & Steitz, 1997), and pseudouridine formation by snoRNA members of the Box H/ACA family (Ganot et al+, 1997;Ni et al+, 1997;Smith & Steitz, 1997)+ The function of these modifications in rRNA is not yet understood, and the snoRNAs utilized for rRNA modifications are dispensable+ In contrast, there are a handful of snoRNAs that are essential for viability of the cell, and are required for rRNA processing events that remove the external transcribed spacers and internal transcribed spacers from the rRNA precursor (summarized in Gerbi, 1995;Maxwell & Fournier, 1995;Sollner-Webb et al+, 1995;Venema & Tollervey, 1995)+ These include U3 (Kass et al+, 1990;Savino & Gerbi, 1990;Hughes & Ares, 1991;Hughes, 1996), U8 (Peculis & Steitz, 1993, U14 (Jarmolowski et al+, 1990;Li et al+, 1990;Li & Fournier, 1992;Liang & Fournier, 1995;Dunbar & Baserga, 1998;Lange et al+, 1998), U22 (Tycowski et al+, 1994), and E1 (ϭU17), E2, and E3 (Mishra & Elicieri, 1997)+ U3 and U14 are used for rRNA processing both in metazoa and in yeast, but the other snoRNAs listed above have only been identified in metazoa+ There are some additional snoRNAs that are essential for rRNA processing that have only been found in yeast+ Of all the snoRNAs that have been identified, U8...…”
Section: Introductionmentioning
confidence: 99%
“…The nucleolus is a prominent organelle in the nucleus of eukaryotic cells+ It is the site of ribosome biogenesis, which involves ribosomal RNA (rRNA) synthesis, modification and processing, and association with ribosomal proteins+ Several of these events are mediated by small nucleolar RNAs (snoRNAs)+ There are about 200 snoRNA species in the nucleolus, most of which are used to guide the modifications that occur on pre-rRNA: 29-O-ribose methylation by snoRNA members of the Box C/D family (Cavaillé et al+, 1996;Kiss-László et al+, 1996Maden, 1996;Nicoloso et al+, 1996;Tollervey, 1996;Tycowski et al+, 1996;Maden & Hughes, 1997;Smith & Steitz, 1997), and pseudouridine formation by snoRNA members of the Box H/ACA family (Ganot et al+, 1997;Ni et al+, 1997;Smith & Steitz, 1997)+ The function of these modifications in rRNA is not yet understood, and the snoRNAs utilized for rRNA modifications are dispensable+ In contrast, there are a handful of snoRNAs that are essential for viability of the cell, and are required for rRNA processing events that remove the external transcribed spacers and internal transcribed spacers from the rRNA precursor (summarized in Gerbi, 1995;Maxwell & Fournier, 1995;Sollner-Webb et al+, 1995;Venema & Tollervey, 1995)+ These include U3 (Kass et al+, 1990;Savino & Gerbi, 1990;Hughes & Ares, 1991;Hughes, 1996), U8 (Peculis & Steitz, 1993, U14 (Jarmolowski et al+, 1990;Li et al+, 1990;Li & Fournier, 1992;Liang & Fournier, 1995;Dunbar & Baserga, 1998;Lange et al+, 1998), U22 (Tycowski et al+, 1994), and E1 (ϭU17), E2, and E3 (Mishra & Elicieri, 1997)+ U3 and U14 are used for rRNA processing both in metazoa and in yeast, but the other snoRNAs listed above have only been identified in metazoa+ There are some additional snoRNAs that are essential for rRNA processing that have only been found in yeast+ Of all the snoRNAs that have been identified, U8...…”
Section: Introductionmentioning
confidence: 99%
“…It was observed by many groups that several of the intron-encoded, fibrillarin-associated snoRNAs contain relatively large stretches of perfect or nearperfect complementarity with rRNA, in some cases up to 22 nucleotides of perfect complementarity (reviewed in references 2 and 22). Kiss-Laszlo et al (16) recently showed that base pairing between the snoRNA and rRNA directs the site of 2ЈO methylation of a nucleotide in rRNA based on the alignment of the conserved box D element in the snoRNA. Thus, each of the snoRNAs in this class is thought to direct the placement of specific 2ЈO-methyl modifications in rRNA.…”
mentioning
confidence: 99%
“…Thus, each of the snoRNAs in this class is thought to direct the placement of specific 2ЈO-methyl modifications in rRNA. Interestingly, neither the intron-encoded, fibrillarin-associated snoRNAs nor the methylation events that they direct appear to be critical for pre-rRNA processing (16).…”
mentioning
confidence: 99%
“…We previously showed that U16 snoRNA is released from its intron precursor by a major pathway consisting of endonucleolytic cleavages of the pre-mRNA and that this processing is alternative to splicing (Caffarelli et al+, 1996)+ We also described two major features of the two conserved box C/D elements: (1) they are indispensable for both correct processing and stability of the snoRNA; (2) they function as binding sites for the proteins p68 and fibrillarin (Caffarelli et al+, 1998)+ To assess whether, besides the boxes, additional sequence/structural elements are required for processing commitment and/or stability of U16 snoRNA, an extensive mutational analysis was carried out+ Several deletion mutants, both in pre-mRNAs and in small nucleolar RNAs, were constructed and tested in vivo by microinjection into X. laevis oocytes+ The structure of U16 snoRNA (see schematic representation in Fig+ 1A) was deduced from in vitro and in vivo RNase footprinting (Prislei et al+, 1992) and was found to match the conserved stem-loop structure+ Similar to other box C/D snoRNAs (U3, U14, U15, U18, U20) U16 also contains an internal stem that is highly conserved from Xenopus to human (Fragapane et al+, 1993)+ U16 snoRNA contains two regions of rRNA complementarity+ The first one (11 nt long) defines a methylated nucleotide on the 18S rRNA and is flanked by a box D9 (Kiss-László et al+, 1996), partially exposed in a bulge+ The second region (14 nt long), which spans the apical loop, is complementary to the 28S rRNA but does not identify any known methylated residue+ In addition, no canonical box D is found downstream of this sequence, whose role in rRNA biogenesis still remains to be defined+ Mature U16 snoRNA and its mutant derivatives are schematically represented in Figure 1B and in the lower part of Figure 2A+ All mutants include the 4-nt long 59-39 terminal stem, the properly positioned boxes C and D, and the variable length of box C/D flanking regions+ The ⌬as RNA mutant is 83 nt long+ It includes the region complementary to 18S rRNA, the flanking box D9, and the entire internal stem of U16; the apical loop structure, containing the sequence complementary to 28S rRNA, is deleted+ The M6 RNA is 72 nt long and differs from ⌬as RNA in the length of the internal stem, which was reduced from 12 bp to 6 bp+ The MD9 RNA is a derivative of M6, in which the sequence CCCC is substituted for CCUA in box D9+ The M1 RNA is 53 nt FIGURE 1. A: Representation of U16 snoRNA secondary structure as deduced by phylogenetical, mutational, and RNase footprinting analyses (Prislei et al+, 1992;Fragapane et al+, 1993)+ Boxes C, D, and D9 are indicated; the long thick arrows and the short thin ones indicate the internal and the 59-39 terminal stem, respectively+ Dotted lines indicate the regions of complementarity to Xenopus 18S (region spanning nt 445-455 of 18S rRNA) (Salim & Maden, 1981) and 28S (region spanning nt 1608-1620 of 28S rRNA) (Ware et al+, 1983) rRNAs+ B: Schematic representation of mature U16 snoRNA and of its mutant derivatives+ Box C, box D, and box D9 are depicted as open boxes+ Regions indicated as 18S and 28S are complementary to Xenopus 18S rRNA and to 28S rRNA, respe...…”
Section: P62 Is a Novel Component Of U16 Snornpmentioning
confidence: 76%
“…Nuclei of eukaryotic cells contain a large number of small nucleolar RNAs (snoRNAs) that actively participate in ribosome biogenesis+ All of them, with the exception of MRP RNA (Maxwell & Fournier, 1995;Tollervey & Kiss, 1997), can be grouped into two major families that are structurally and functionally distinct: the box C/D and the box H/ACA snoRNAs+ Although some snoRNAs belonging to both classes are required for cleavage of pre-rRNA (box C/D: U3, U8, U14, U22; box H/ACA: snR30, U17, E2, E3; Hughes & Ares, 1991;Morissey & Tollervey 1993;Maxwell & Fournier, 1995;Enright et al+, 1996;Borovjagin & Gerbi, 1999), most of them function as guides in posttranscriptional modification of pre-rRNA+ The box C/D snoRNAs direct the site-specific 29-O-methylation of pre-rRNA (Cavaillé et al+, 1996;Kiss-László et al+, 1996;Maden, 1996;Nicoloso et al+, 1996;Tollervey, 1996;Tycowski et al+, 1996;Bachellerie & Cavaillé, 1997;Maden & Hughes, 1997;Kiss-László et al+, 1998), whereas the box H/ACA snoRNAs are involved in site-specific conversion of uridines into pseudouridines (Balakin et al+, 1996;Ganot et al+, 1997)+ A stem-loop structure has been proposed for the members of box C/D snoRNA family (Bachellerie et al+, 1995); this model predicts that the 59 and 39 termini of the snoRNA form a short terminal stem (at least 4 bp) that delimitates a loop region where two highly conserved sequence elements (boxes C and D) are localized+ The boxes are positioned on opposite sides of the loop and are brought in close proximity by the terminal stem+ In many cases an internal stem can further stabilize this structure (Tycowski et al+, 1993;Nicoloso et al+, 1994)+ In intron-encoded snoRNAs, where a canonical terminal stem is absent, external intronic complementary sequences have been shown to perform the function of juxtaposing the boxes C and D (T+ Villa, pers+ comm+)+ Extensive mutagenesis analysis carried out on mouse U14 snoRNA (Xia et al+, 1997) has led to the definition of a "minimal core motif" including the conserved boxes and the terminal stem+ This motif is essential for the biosynthesis (Caffarelli et al+, 1996;Watkins et al+, 1996;Xia et al+, 1997), the metabolic stability …”
Section: Introductionmentioning
confidence: 99%